Potential effects of punicalagin on new zealand white rabbits exposed to bisphenol A - Gülay, Mehmet Şükrü; Gülay, Özlem Yildiz; Candan, Gülşah (My University)
The possible effects of punicalagin on some oxidant-antioxidant enzymes and biochemical parameters in bisphenol A (BPA)-treated rabbits were investigated. Animals were randomly divided into 4 groups, each containing 6 rabbits: Control (C; corn oil and distilled water), BPA (BPA; 20 mg/kg BPA in corn oil and distilled water), the punicalagin (PUN; corn oil and 2 mg/kg punicalagin in distilled water), and BPA-punicalagin (B+P; 20 mg/kg BPA in corn oil and 2 mg/kg PUN in distilled water) groups. Daily treatments continued for 9 weeks and doses were adjusted according to body weights measured for each week. At the end of the study, hematological, biochemical, and oxidant-antioxidant parameters were measured from blood and tissue samples. The difference in the levels of plasma bilirubin, albumin, total plasma protein, Mg, P, Ca, Na, K, and levels of glutathione peroxidase in plasma, liver, and kidney were non-significant (p>0.1). However, oral BPA administration adversely affected serum cholesterol, LDL, HDL, amylase, lipase, CRP, and GGT concentrations. Likewise, malondialdehyde, catalase, and superoxide dismutase levels in the kidney and liver were also negatively altered by BPA (p<0.05). Significant improvements in these parameters were apparent in the B+P group. The data generated here showed that punicalagin possessed a beneficial impact on potentially reducing the possible toxic effects of BPA in rabbits.

Çalışmada, BPA verilen Yeni Zelanda tavşanlarında punikalajininbazı oksidan-antioksidan enzimler ile bazı biyokimyasal parametreler üzerine olası etkilerin incelendi. Bu amaçla 2 hafta boyunca laboratuvar koşullarına alıştırılan tavşanlar, her grupta 6 tavşan olacak şekilde rastgele 4 gruba ayrıldı: Kontrol (C; mısır yağı ve distile su), BPA (BPA; mısır yağı içerisinde 20 mg/kg BPA ve distile su), punikalajin (PUN; mısır yağı ve distile su içerisinde 2 mg/kg punikalajin), ve BPA-punikalajin grubu (B+P; mısır yağı içerisinde 20 mg/kg BPA ve distile su içerisinde 2 mg/kg PUN). Uygulamalar 9 hafta boyunca günlük olarak yapıldı ve haftada bir kez yapılan tartımlara göre dozlar ayarlandı. Çalışma sonunda alınan kan ve doku örneklerinden hematolojik, biyokimyasal ve oksidanantioksidan parametrelerin ölçümleriyapıldı. Analizler neticesinde plazma bilirubin, albümin ve toplam plazma protein düzeyleri ile Mg, P, Ca, Na, K, seviyelerinde herhangi bir istatistiki farka rastlanmazken, farklı gruplardaki plazma, karaciğer ve böbrek glutatyon peroksidaz değerleri de önemsiz bulundu (p>0,1). Oral BPA uygulamaları serum kolesterol, LDL, HDL, amilaz, lipaz, CRP, GGT seviyeleri ile karaciğer ve böbrek dokusundaki malonildialdehit, katalaz ve süperoksit dismütaz seviyelerini olumsuz etkiledi (p<0,05). B+P grubunda ise bu parametrelerde önemli ölçüde iyileşme gözlendi. Elde edilen sonuçlar, BPA'nın erkek tavşanlarda yol açtığı olası toksik etkilerin punikalajin tedavisi ile önemli ölçüde düzeltilebileceğini gösterdi.
Bisfenol A’ya maruz kalan erkek Yeni Zelanda tavşanlarında punikalajinin potansiyel etkileri
Keywords: Antioxidants; Cholesterol; Oxidant-Antioxidant Enzymes; Polyphenols; Toxication; Antioksidanlar; Kolesterol; Oksidan-Antioksidan Enzimler; Polifenoller; Toksikasyon